MORPHOLOGICAL CHANGES IN CARDIAC TISSUE AFTER MECHANICAL TRAUMA UNDER GENERAL ANESTHESIA: AN EXPERIMENTAL ANALYSIS - Vohidov Bekzod Rafiq o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This experimental study investigated morphological changes in rat heart tissue subjected  to  mechanical  trauma  under  general  anesthesia  (nitrous  oxide  –  N₂O). According to histological analysis, dystrophic changes in cardiomyocytes, karyolysis, cytolysis,  focal  necrosis,  interstitial  edema,  venous  congestion,  and  leukocytic infiltration were identified. These structural changes may impair cardiac function and are essential indicators for evaluating the effects of anesthesia. The study results are significant  for  early  detection  and  prevention  of  cardiac  complications  in  clinical practice.